2020
DOI: 10.22207/jpam.14.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Livestock Manure as Potential Reservoir of CTX-M Type Extended-spectrum β-lactamase Producing Escherichia coli and Klebsiella pneumoniae Associated with Carbapenemase Production

Abstract: Increasing faecal carriage rate of extended-spectrum beta-lactamase (ESBL) producing Escherichia coli (ESBL-EC) and Klebsiella pneumoniae (ESBL-KP) among livestock is responsible for abundance of these bacteria in livestock manure which is being extensively used as organic fertilizer in developing countries including India. Use of this manure can be a potential source for spread of these microorganisms to the human community, posing a serious public health threat especially, to manure handlers. There is paucit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In pig manure, for example, several studies detected multidrug-resistant Salmonella enteritidis and other Salmonella species (Supplementary Table 2) and Salmonella enterica and its serovars that are known to cause human gastroenteritis are known to originate from pigs (Kingsley and Bäumler, 2000). A 3-year study of drug resistance in cattle manure in Northern India regions revealed a high prevalence of extended-spectrum β-lactamase and carbapenemase-producing E. coli and K. pneumoniae isolates, of which several isolates exhibited co-resistance to cephalosporin and noncephalosporin antibiotics (Devi et al, 2020). In another study across poultry farms in Ghana, more than 35% of the total Staphylococcus species isolated from the manure were resistant to antibiotics such as tetracycline, doxycycline and oxacillin (Boamah et al, 2017).…”
Section: Antibiotics and Amr In Animal Manurementioning
confidence: 99%
“…In pig manure, for example, several studies detected multidrug-resistant Salmonella enteritidis and other Salmonella species (Supplementary Table 2) and Salmonella enterica and its serovars that are known to cause human gastroenteritis are known to originate from pigs (Kingsley and Bäumler, 2000). A 3-year study of drug resistance in cattle manure in Northern India regions revealed a high prevalence of extended-spectrum β-lactamase and carbapenemase-producing E. coli and K. pneumoniae isolates, of which several isolates exhibited co-resistance to cephalosporin and noncephalosporin antibiotics (Devi et al, 2020). In another study across poultry farms in Ghana, more than 35% of the total Staphylococcus species isolated from the manure were resistant to antibiotics such as tetracycline, doxycycline and oxacillin (Boamah et al, 2017).…”
Section: Antibiotics and Amr In Animal Manurementioning
confidence: 99%
“…E. coli and K. pneumoniae strains growing in ESBL screening media and in carbapenemase screening media were identified as potential ESBL and carbapenemase producing strains respectively. 12,13…”
Section: Processing Of Samples For Screening Of Esbl and Carbapenemase Producing E Coli And K Pneumoniae Isolatesmentioning
confidence: 99%
“…coli and K. pneumoniae isolates from CR screening medium i.e., Mac-ETP were initially subjected to modified Hodge test (MHT) as described earlier. 13 However, all the E. coli and K. pneumoniae isolated from the Mac-ETP plate were also subjected to revalidation of carbapenemase production on the basis of Carba-NP test in accordance with new CLSI guidelines. Both the methods employed K. pneumoniae ATCC BAA 1705 and E. coli ATCC 25922 as positive and negative control strains respectively.…”
Section: Carbapenemase Productionmentioning
confidence: 99%
“…ESBL production among the E. coil isolates screened by the screening media was confirmed by phenotypic confirmatory tests i.e., double disc synergy test (DDST) as described earlier 11,12 using two pairs of antibiotic discs, ceftazidime (30 µg) and ceftazidime plus clavulanic acid (30 µg plus 10 µg) discs and cefotaxime (30µg) and cefotaxime plus clavulanic acid (30 µg plus 10 µg) discs. K. pneumoniae ATCC 700603 and E. coli ATCC 25922 strains were used as ESBL-positive and ESBLnegative control strains respectively.…”
Section: Phenotypic Confirmation Of E Coil Isolates For Esbl Productionmentioning
confidence: 99%
“…Phenotypically confirmed ESBL-EC were subjected to PCR assay as described earlier to detect the presence of bla TEM , bla SHV and bla CTX-M genes using pre-published primer sequences, viz. TEM primers (TEM forward ATGAGTATTCAACATTTCCGTG, TEM reverse TTACCAATGCTTAATCAGTGAG) amplifying 840-bp fragment, SHV primers (SHV forward ATTTGTCGCTTCTTTACTCGC, SHV reverse TTTATGGCGTTACCTTTGACC) amplifying 1051-bp fragment and CTX-M primers (CTX-M forward TTTGCGATGTGCAGTACCAGTAA, CTX-M reverse CGATATCGTTGGTGGTGCCATA) amplifying 544-bp fragment 11,13 .…”
Section: Molecular Identification Of Bla Tem Bla Shv Bla Ctx-m and Bla Ndm Genesmentioning
confidence: 99%